Achieving weak anisotropy in N-type I-doped SnSe polycrystalline thermoelectric materials. Issue 15 (December 2022) - Abbas, Adeel; Xu, Zhuoming; Nisar, Mohammad; Li, Delong; Li, Fu; Zheng, Zhuanghao; Liang, Guangxing; Fan, Ping; Chen, Yue-Xing
Abstract: SnSe is a very strong anisotropic material; sometimes, strong anisotropy is unenviable for producing parts of thermoelectric (TE) devices. In order to study the efficient preparation of high-performance n-type polycrystalline SnSe with weak anisotropy, in this work, we combine mechanical alloying at 450 RPM for 10 h and spark plasma sintering at 773 K under 50 MPa pressure for the preparation of polycrystalline SnSe 0.95- x I x ( x = 0, 0.01, 0.02, 0.03) samples, and investigate the TE properties. The prepared samples show very weak anisotropy. With iodine doping, increased carrier concentration is observed, in agreement with DFT calculations. A peak ZT ≈ 1.02 at 723 K is observed with I-doping of x = 0.02, which is about 225% higher than that of undoped sample with ZT ≈ 0.31 at 723 K in parallel direction, mainly attributed to the enhanced power factor and about 56% reduced thermal conductivity from 0.68 Wm −1 K −1 to 0.30 Wm −1 K −1 . TE properties in both directions are not much different, and the ratios of electrical and thermal conductivities in both directions are very close to unity.